2016
DOI: 10.1016/j.bpsc.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Within- and Between-Session Changes in Neural Activity During Emotion Processing in Unipolar and Bipolar Depression

Abstract: Background Bipolar disorder (BD) and unipolar depression (UD) can be difficult to distinguish clinically, particularly during episodes of depression. In this study we test for differences between BD, UD, and healthy control (HC) adults regarding within- and between-session changes in BOLD response during implicit emotional processing. Methods During fMRI, HC adults (N=19) and depressed adults with UD (N=19) and BD (N=16) performed an implicit emotion-processing task. Each participant was scanned twice, separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Existing (non-connectomic) studies have reported different baseline fMRI activations to cognitive [177] and emotional-tasks [178, 179] in those HR individuals who later develop a first depressive episode. Repeat functional imaging assays also suggest different trajectories of functional activation in the striatum and insula of unipolar versus bipolar depression [180]: morphological studies using sMRI likewise suggest predictors of first episode mood disorders in HR populations, [181, 182] as well as the likelihood of further mania in those with BD [183]. Moreover, different trajectories of volumetric development have also been observed in HR individuals who developed major depressive disorder relative to those who remained well [181].…”
Section: Challenges and Opportunities In Bd Connectomicsmentioning
confidence: 99%
“…Existing (non-connectomic) studies have reported different baseline fMRI activations to cognitive [177] and emotional-tasks [178, 179] in those HR individuals who later develop a first depressive episode. Repeat functional imaging assays also suggest different trajectories of functional activation in the striatum and insula of unipolar versus bipolar depression [180]: morphological studies using sMRI likewise suggest predictors of first episode mood disorders in HR populations, [181, 182] as well as the likelihood of further mania in those with BD [183]. Moreover, different trajectories of volumetric development have also been observed in HR individuals who developed major depressive disorder relative to those who remained well [181].…”
Section: Challenges and Opportunities In Bd Connectomicsmentioning
confidence: 99%
“…Indeed, recent work suggests that alterations in the time course of brain function across a task, particularly to repeated presentations of emotional faces, may contribute to BD and other psychopathology. In particular, adults with BD, compared to healthy adults, exhibit more rapid attenuation of striatal‐insular connectivity in response to repeated presentation of emotional faces . Similarly, in other disorders, for example, autism, schizophrenia, social anxiety disorder, and post‐traumatic stress disorder, alterations in activation of limbic and prefrontal regions over the course of repeated presentation of emotional faces has been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that time course of activation would differ based on age group and diagnostic status in the amygdala ROI, as well as prefrontal and striatal regions. Since change in brain activation over the course of the task has not previously been studied in youths vs adults with BD compared to healthy youths vs adults, we based these predictions on previous studies investigating average activation in this population. Due to the paucity of research using this analytic method we made no hypotheses regarding differences in directionality for prefrontal and striatal regions, however, we expected youths with BD to display decreased attenuation of activation over time in the amygdala ROIs compared to healthy youths based on findings in children with autism where emotional processing deficits have also been documented .…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have hypothesized that BD may develop a progressive path over time in particular in a subgroup of BD patients who showed initial subtle cognitive impairments and were more likely to develop chronicity [ 22 , 23 ]. In addition, several neuroimaging studies showed specific brain abnormalities in BD in order to validate the neuroprogressive hypothesis underlying this condition, with the most relevant findings referring to the presence of both regional structural and functional alterations, predominantly in the striatal–insular–thalamic and temporo–parietal associated regions [ 24 ], at least in a specific subgroup of subjects.…”
Section: Introductionmentioning
confidence: 99%